Synthesis and Antimicrobial Screening of 2-Methyl- 3-[5-substituted phenyl-1,3,4-oxadiazol-2-yl]-1H-indoles - BHASKAR, V.H.; SUBRAMANIYAM, S.; THAKOR, R.S.; JAYAKAR, B. (Asian Journal of Chemistry, 2010)
Some 2-methyl-3-[5-substituted phenyl-1,3,4-oxadiazol-2-yl]-1H-indoles (Va-e) were synthesized by reacting oxoacetohydrazide (IV) with various aromatic acid in presence of phosphorus oxychloride. The structures of the compounds have been established on their analytical and spectral data. All the compounds have been screened for their antimicrobial activity against Bacillus subtillis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Aspergillus niger and Candida albicans. Compounds Ve and Vb exhibited interesting results.